2009
DOI: 10.1002/cncr.24065
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic neuroendocrine tumors

Abstract: BACKGROUND: Although surgical resection is generally recommended for patients with localized pancreatic neuroendocrine tumors (PNETs), the impact of resection on overall survival is unknown. The authors investigated the survival advantage of pancreatic resection using a national database. METHODS: This is a retrospective survival analysis of patients with PNETs from the Surveillance, Epidemiology, and End Results database (1988‐2002). RESULTS: A total of 728 patients with PNETs were identified with a median su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 271 publications
(83 citation statements)
references
References 31 publications
3
79
0
1
Order By: Relevance
“…The site of primary NETs has been identified as an important prognostic feature of NETs in previous studies [15,16]. NETs are diverse in their site of origin and clinical behavior, and researchers have found that pancreatic primary tumor localization is a risk factor for decreased survival [17,18,19,20]. A comparison of P-NETs and GE-NETs exhibited higher NLR and PLR levels in patients with P-NETs, which was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The site of primary NETs has been identified as an important prognostic feature of NETs in previous studies [15,16]. NETs are diverse in their site of origin and clinical behavior, and researchers have found that pancreatic primary tumor localization is a risk factor for decreased survival [17,18,19,20]. A comparison of P-NETs and GE-NETs exhibited higher NLR and PLR levels in patients with P-NETs, which was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Hill et al demonstrated that surgical resection was associated with improved survival for patients with localized, regional, or metastatic PNETs. 21 However, they did not examine the subset of patients with nonfunctional tumors ≤2 cm. The benefit of surgery in this population is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…[16,36,35] Even when liver metastases cannot be completely resected, retrospective studies suggest that resection of the primary tumor prolongs survival of patients with SBNETs and PNETs. [13,16,15,36,14] Knowing with high positive predictive value that an unknown metastasis arose from an SBNET primary therefore presents a strong indication for surgical exploration. A criticism of using such an algorithm for surgical planning is that because most PNETs are visualized on CT imaging, unknown-primary NETs are already likely to be of small bowel origin.…”
Section: Discussionmentioning
confidence: 99%